A new genus and species of Encyrtidae (Hymenoptera: Chalcidoidea) with a four-segmented funicle from late Eocene Baltic amber - Simutnik, Serguei A.; Pankowski, Madeline V.; Perkovsky, Evgeny E. (Zootaxa, 2023)
Electrocerus brevifuniculatus Simutnik gen. et sp. nov. is described and illustrated based on a female specimen from late Eocene Baltic amber. Placement of the new genus in the subfamily Encyrtinae is supported by the presence of a filum spinosum on the linea calva and the hypopygium not reaching the metasomal apex. A key to the genera of late Eocene Encyrtinae is provided. The new taxon differs from all known extinct and most extant encyrtids by its four-segmented female funicle.